2019
DOI: 10.1002/adtp.201900105
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Two Novel Small Compounds that Inhibit Liver Cancer Formation in Zebrafish and Analysis of Their Conjugation to Nanodiamonds to Further Reduce Toxicity

Abstract: Liver cancer, which is ranked fourth in cancer-related mortality worldwide, lacks effective therapeutic treatments. The development of new targeted therapies for liver cancer is urgently needed. The zebrafish is an excellent preclinical model organism for drug screening. Therefore, in a zebrafish model, hundreds of small molecules are screened, and two compounds (LIB1O0078 and LIB1O0144) are identified as the strongest inducers of antiangiogenic effects without side effects. LIB1O0078 exhibits better antiproli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…After fixation by 4% paraformaldehyde on coverslips, these neutrophils were then stained with rabbit anti-mouse citrulline Histone H3 antibody (1:1000) and 4',6-diamidino-2-phenylindole (DAPI, 5 μl/ml). A fluorescence microscope (Nikon Eclipse E800; Nikon Taiwan, Taipei, Taiwan) ( 51 ) was used for obtaining the NETosis images. To analyze mitochondria membrane potential, superoxide, and membrane potential levels, mitochondria labeling reagents MitoTracker™ Green FM (Thermo Fisher Scientific, Waltham, MA, USA), MitoSOX™ Red mitochondrial superoxide indicator (Thermo Fisher Scientific), MitoTracker™ Red CMXRos (Thermo Fisher Scientific) were used according to the manufacturer's instructions ( 33 , 52 ).…”
Section: Methodsmentioning
confidence: 99%
“…After fixation by 4% paraformaldehyde on coverslips, these neutrophils were then stained with rabbit anti-mouse citrulline Histone H3 antibody (1:1000) and 4',6-diamidino-2-phenylindole (DAPI, 5 μl/ml). A fluorescence microscope (Nikon Eclipse E800; Nikon Taiwan, Taipei, Taiwan) ( 51 ) was used for obtaining the NETosis images. To analyze mitochondria membrane potential, superoxide, and membrane potential levels, mitochondria labeling reagents MitoTracker™ Green FM (Thermo Fisher Scientific, Waltham, MA, USA), MitoSOX™ Red mitochondrial superoxide indicator (Thermo Fisher Scientific), MitoTracker™ Red CMXRos (Thermo Fisher Scientific) were used according to the manufacturer's instructions ( 33 , 52 ).…”
Section: Methodsmentioning
confidence: 99%
“…Zebrafish have been used to study engineered nanomaterials and NPs in various fields, such as biomedical research [38,[56][57][58] and studies on environmental health and safety [59,60]. Most relevant studies have reported that TiO 2 NPs are toxic and induce mortality in zebrafish embryos but are less toxic and cause less mortality in adult zebrafishes; this finding is likely attributable to the fact that these studies have tended to focus only on observations of acute stimulation [18,[61][62][63][64].…”
Section: Discussionmentioning
confidence: 99%
“…Adult wild zebrafish were used in the experiment and were kept in a semistatic system with charcoal-filtered tap water (pH 7.0-7.4) at 28 ± 0.5˚C as recommended in a previous study PLOS ONE [38], with a 12-h light-12-h dark (12L:12D) photocycle (Classictone incandescent lamp, Philips; Taiwan, without illuminating UV to avoid UV-induced photocatalysis [5,11,12,33,39,40]). The fish were fed newly hatched brine shrimp and pellet food (Zeigler Brothers, Gardners, PA, USA) and were kept in 30-L glass tanks with 20 L of water per tank.…”
Section: Zebrafish Maintenance and Experimental Proceduresmentioning
confidence: 99%
“…To prepare the stock solutions of 10 mg/mL TiO 2 (5 and 60 nm; Nanostructured & Amorphous Materials, Katy, TX, USA), 10 mg/mL NDs (5-200 nm; Kay Diamond Products, Boca Raton, FL. USA) ( 56 , 57 ), and red fluorescent NDs (50 nm; brFND-50, nitrogen-vacancy NV centers per particle > 100, FND Biotech, Taipei, Taiwan) ( 58 , 59 ), the nanoparticles (NPs) were dispersed in distilled deionized water under sonication (80 W/L, 46 kHz) for 20 min. Test NP solutions were prepared immediately before use by dilution of the stock solutions with distilled deionized water and sonication (80 W/L, 46 kHz) for 20 min ( 60 ).…”
Section: Methodsmentioning
confidence: 99%